Application of a Peeler Blade and Adaptive Spring Mechanism in a Tuber Peeling Machine - Fadwah Maghfurah; Farhan Rian Ramadhan; Windarta (Jurnal Teknologi, 2026)
The development of friction-based tuber peeling machines requires an integrated approach involving mechanical design, theoretical analysis, and experimental validation to achieve an optimal balance between productivity and peeling quality. This study aims to design and evaluate the performance of a tuber peeling machine incorporating a peeler blade and an adaptive spring-loaded mechanism. The methodology included kinematic analysis, belt–pulley transmission design (2:1 transmission ratio producing a shaft speed of 710 rpm), motor torque and power calculations (effective torque of 4.48 N·m), friction and normal force analyses as the primary peeling mechanisms, and structural evaluations of the machine frame and shaft. The analytical results indicated that the ASTM A36 steel frame exhibited a maximum bending stress of 10.2 MPa, a factor of safety of 24.5, and a maximum deflection of 0.77 mm. Meanwhile, the shaft experienced a deflection of 0.22 mm and operated at only 35% of its critical speed (2015 rpm), confirming both structural and dynamic stability. Experimental validation demonstrated that processing capacity increased with rotational speed, reaching a maximum value of 17.83 kg h⁻¹ at 400 rpm compared with 13.67 kg h⁻¹ at 300 rpm. In contrast, peeling efficiency exhibited a non-linear trend, achieving an optimum value of 95.67% at 300 rpm and decreasing significantly at 400 rpm, particularly for potatoes (75.70%), due to the occurrence of over-cutting. These findings reveal a trade-off between processing capacity and peeling efficiency, indicating that optimal machine performance depends on both material characteristics and operating conditions. Overall, the developed peeling system demonstrated stable operation, adaptive performance, and compliance with technical and functional requirements for small- to medium-scale agricultural processing applications.